The use of information technologies to predict and diagnose the psychological trauma of servicemen – combatants - O. S. Kolesnichenko; S. A. Gorelyshev (Law and Safety)
Based on the analysis of existing developments in the field of automation of psychological and psycho-physiological testing procedures, as well as own empirical studies of combat psychological trauma of servicemen – combatants, the authors within the scientific research “Development of Preventive Program of Post-Trauma Stress Disorders of Servicemen of the National Guard of Ukraine”, have offered own approach to the creation of the complex of automated methods for determining resistance to psychological trauma by the combat experience, presence / absence of the features of post-traumatic stress disorder, presence / absence of psychological trauma of the combat experience